Starting gastrointestinal endoscopy in a lower middle-income country in Africa: Training, creating an endoscopy facility and developing telemedicine - Campos, Sara T.; Barreto, Lagchar; Fernandes, Vítor; Meira, Tânia; Portela, Francisco; Carreira, Cátia; Nunes, Ana Margarida; d’Apresentação, Pascoal; Barreto, Laurinda; Lima, Wrciley; da Costa, Dʼjarda; Zhaky, Ahmed; Freitas, Paulo (Endoscopy International Open, 2022)
Background and study aims The prevalence of digestive diseases seems to be high in African countries. Nonetheless, the human and material resources are scarce. The aim of the Portuguese volunteering project described in this report was to develop the specialty of digestive endoscopy in Sao Tome and Principe, a lower-middle-income country in Africa.Methods Beginning by assessing the local needs and available resources and managing immediate issues related to this field, we aimed to provide the tools necessary to improve gastroenterological and endoscopic care in the country. The first step included training of the local teams, through the development and accomplishment of an adapted curriculum for a 3-year medical gastroenterological fellowship and a short-term nursing fellowship, both in Portugal, and the organization of regular gastroenterological and endoscopic theoretical and practical sessions in Sao Tome and Principe. Second, the endoscopy facilities of the unit were significantly optimized. Third, a web platform was designed to provide telemedicine incorporating real-time endoscopic imaging available remotely.Results Through these sequential steps achieved in collaboration with Portuguese and local teams, this 5-year project provided the basis for gastroenterology care in this country.Conclusions At the present time, Sao Tome and Principe has an autonomous, efficient and skilled team and unit to provide care for patients with gastrointestinal diseases who need endoscopic procedures.